Characteristics of bone metabolism in women with post-menopausal osteoporosis in a hospital from Lima - Hidalgo García, Arquímedes (2019)
Introduction: In our context, there are no studies which had evaluated the markers of bone turnover in postmenopausal women with osteoporosis, considering the high rate of morbidity and mortality associated with fragility fractures. Objective: To know the biochemical features of bone metabolism in women with postmenopausal osteoporosis. Methods: A cross-sectional study. 49 women with postmenopausal osteoporosis were included. Bone mineral density in spine, hip and forearm was measured by dual x-ray absorptiometry. Calcium, phosphorus, osteocalcin, alkaline phosphatase, vitamin D and paratohormone were measured in blood. N-telopeptide of collagen type I, calcium and phosphorus were measured in urine by conventional methods. Results: The average age of the participants was 59,1± 7,5 years. The average time since menopause was 12,0 ± 7,9 years. All had osteoporosis in forearm; 46,9% had insufficient levels of vitamin D and 8,2% had deficient values. The osteocalcin was normal in 73,5%, decreased in 20,1% and increased in 6,4% participants. Age showed statistically significant correlation with serum parathyroid hormone and was negatively correlated with vitamin D. The time of menopause had a positive and statistically significant correlation with alkaline phosphatase. Conclusion: The extension of osteoporosis had a positive correlation with older age and longer menopause. The bone turnover markers provide complementary information to bone densitometry.